A highly sensitive CE‐chemiluminescence method for the determination of sympathomimetic drugs in urine samples by a facile precolumn derivatization using acridinium ester. Issue 7 (23rd October 2013) - Wang, Zuorong; Yue, Huan; Wang, Yonghong; Wang, Lin; Fu, Zhifeng; Phillips, Terry M.
<x xml:space="preserve">Abstract</x> As one of the most sensitive detection mode for CE, chemiluminescence (CL) detection is less developed compared to some other detection modes such as MS and LIF, despite its low equipment cost and simple design. The fact is partly due to the limitation of CL systems suitable for CE. In this paper, a highly sensitive CE‐CL strategy was established for the determination of dopamine (DA) and cimbuterol (CM) using acridinium ester as derivatization reagent. Catalyst was not required in this CL detection system. Also, a good sensitivity was obtained due to its quite low background and strong signal. Under the optimal conditions, the presented method has been successfully applied to analyze DA and CM with LODs (S/N = 3) of 2.0 and 0.50 ng/mL, respectively. The linear ranges were 5.0–1500 ng/mL and 2.0–1000 ng/mL for DA and CM, respectively. To validate our method, the levels of DA in human urine samples were detected by this method, and the results showed acceptable accordance with those of ELISA. All the analysis procedure could be completed in 400 s, and the results showed satisfactory sensitivity and selectivity. The approach could also be further extended to rapid analysis of many other compounds including primary and second amines in clinical medicine and biopharmaceutical analysis using acridinium ester as CL derivatization reagent.